Diversity and function of maize pollen coat proteins: from biochemistry to proteomics - Gong, Fangping; Wu, Xiaolin; Wang, Wei (Frontiers in Plant Science, 2015)
Maize (Zea mays L.) is globally cultivated as one of the most important grain crops. As a wind-pollinated species, maize produces a large quantity of pollen grains that heavier and larger compared to Arabidopsis. Maize is an important model plant in pollen biology of monocots. The pollen coat, the outermost layer of pollen, plays a vital role in pollen-stigma interactions and successful fertilization. Pollen coat proteins (PCPs), which confer species specificity, are required for pollen adhesion, recognition, hydration and germination on the stigma. Thus, PCPs have attracted intensive research efforts in plant science for decades. However, only a few PCPs in maize have been characterized to date, whereas the functions of most maize PCPs remain unclear. In this review, we summarize the current knowledge of maize PCPs with regard to protein constituents, synthesis and transport, and functions by comparison with the model plant Arabidopsis thaliana and Brassica plants. An understanding of the comprehensive knowledge of maize PCPs will help to illuminate the mechanism by which PCPs are involved in pollen-stigma interactions in maize and other crop plants.